The effects of age structure on economic growth: An application of probabilistic forecasting to India - Alexia Prskawetz; Tomas Kögel; Warren C. Sanderson; Sergei Scherbov (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2004)
During recent years there has been an increasing awareness of the explanatory power of demographic variables in economic growth regressions. We estimate a new model of the effects of age structure change on economic growth. We use the new model and recent probabilistic demographic projections for India to derive the uncertainty of predicted economic growth rates caused by the uncertainty in demographic developments.
Keywords: 300; economic growth; age structure; probabilistic demographic projections; India